Properties of the input pattern fault model - Blanton, R.D.; Hayes, J.P. (Proceedings International Conference on Computer Design VLSI in Computers and Processors, 1997)
Recent work in IC failure analysis strongly indicates the need for fault models that directly analyze the function of circuit primitives. The input pattern (IP) fault model is a functional fault model that allows for both complete and partial functional verification of every circuit module, independent of the design level. We describe the IP fault model and provide a method for analyzing IP faults using standard SSL-based fault simulators and test generation tools. The method is used to generate test sets that target the IP faults of the ISCAS85 benchmark circuits and a carry-lookahead adder. Improved IP fault coverage for the benchmarks and the adder is obtained by adding a small number of test patterns to tests that target only SSL faults. We also conducted fault simulation experiments that show IP test patterns are effective in detecting non-targeted faults such as bridging and transistor stuck-on faults. Finally, we discuss the notion of IP redundancy and show how large amounts of this redundancy exist in the benchmarks and in SSL-irredundant adder circuits.